2019
DOI: 10.1186/s13023-019-1163-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of structural progression between ciliopathy and non-ciliopathy associated with autosomal recessive retinitis pigmentosa

Abstract: Background To evaluate and compare the progression of ciliopathy and non-ciliopathy autosomal recessive Retinitis Pigmentosa patients (arRP) by measuring the constriction of hyperautofluorescent rings in fundus autofluorescence (FAF) images and the progressive shortening of the ellipsoid zone line width obtained by spectral-domain optical coherence tomography (SD-OCT). Results For the ciliopathy group, the estimated mean shortening of the ellipsoid zone line was 259 μm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Genetic mutations that lead to retinitis pigmentosa can occur or be transferred by autosomal dominant (AD), autosomal recessive (AR), X-linked, mitochondrial, mosaic, or sporadic inheritance [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Rhodopsin and opsin are the major protein products which synthesized in the photoreceptors [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic mutations that lead to retinitis pigmentosa can occur or be transferred by autosomal dominant (AD), autosomal recessive (AR), X-linked, mitochondrial, mosaic, or sporadic inheritance [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Rhodopsin and opsin are the major protein products which synthesized in the photoreceptors [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Since both alleles are mutants, they progress faster. The average annual EZ loss rate is around 10% [11][12][13][14][15][16][17]. The proteins responsible for the energy cycle are similar to the exosome contents produced by stem cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photoreceptors have cilia tubule functions that provide the transport of opsin and rhodopsin and can be impaired by X-linked mutations-they can be distinguished by the presence of widespread lipofuscin deposits in the fundus examination. The ciliopathy gene mutations have threefold faster progression than non-ciliopathy mutations [23]. Retinitis pigmentosa progresses with an average of 10% annual photoreceptor loss when AD, AR, X-linked, and mitochondrial inheritance patterns are collectively evaluated [6,24,25].…”
Section: Figures 125mentioning
confidence: 99%
“…The recent adaptation of high-throughput DNA sequencing technologies has accelerated the identification of the causative genes of Japanese patients with RP, and these studies have revealed the major causative genes in this population. [4][5][6] Some of these major genes were categorized into the ciliopathy-related genes (e.g., the USH2A, RPGR, RP1, and RP1L1 genes), [7][8][9][10][11][12] and it was also suggested that the function of the EYS protein is associated with the cilia. 1,13,14 Recently, several studies have reported that steep macular curvatures were observed in the eyes of patients with various inherited retinal disorders, including retinal ciliopathy, Joubert syndrome, Leber's congenital amaurosis, and RP without high myopia.…”
mentioning
confidence: 99%